2018
DOI: 10.2147/rrtm.s154501
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and HIV coinfection in sub-Saharan Africa: prevalence, impact, and treatment strategies

Abstract: Malaria and HIV, two of the world’s most deadly diseases, are widespread, but their distribution overlaps greatly in sub-Saharan Africa. Consequently, malaria and HIV coinfection (MHC) is common in the region. In this paper, pertinent publications on the prevalence, impact, and treatment strategies of MHC obtained by searching major electronic databases (PubMed, PubMed Central, Google Scholar, ScienceDirect, and Scopus) were reviewed, and it was found that the prevalence of MHC in SSA was 0.7%–47.5% overall. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 120 publications
3
98
0
Order By: Relevance
“…However, data on IL-27 regulation in clinical malaria is scarce, and to this end, there are no data on IL-27 levels during falciparum malaria in adults. Further, how co-infection with HIV influences IL-27 levels during falciparum malaria is unknown and such knowledge would be of importance in light of a considerable geographic overlap between the two diseases, particularly in sub-Saharan Africa where different interactions between HIV and malaria has been described [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, data on IL-27 regulation in clinical malaria is scarce, and to this end, there are no data on IL-27 levels during falciparum malaria in adults. Further, how co-infection with HIV influences IL-27 levels during falciparum malaria is unknown and such knowledge would be of importance in light of a considerable geographic overlap between the two diseases, particularly in sub-Saharan Africa where different interactions between HIV and malaria has been described [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is fundamental to continually initiate and update data on the burden of malaria among PLWHA to prevent new cases of the disease and guide clinical practice in sub-Saharan Africa, especially in Nigeria (WHO, 2015). The majority of the published articles pay little or no attention to the impact of malaria on HIV, rather on the public health effect of HIV on malaria (Kwenti, 2018). This research study aims to provide additional epidemiological data of malaria among HIV seropositive individuals over five years to establish the trend in prevalence while also putting the seasonal variation into consideration.…”
Section: Scope Of the Studymentioning
confidence: 99%
“…Among patients using antimalarial and antiretroviral medicine simultaneously, a couple of notable adverse reactions to the medication have been documented. Being on cotrimoxazole and sulfadoxine-pyrimethamine at the same time is not advocated during pregnancy, due to the likelihood of sulfonamide associated toxicity (Kwenti, 2018). Studies conducted in Nigeria have reported a high prevalence of malaria among PLWHA; however, a limited clinical association between HIV and malaria has been documented in Nigeria (Olorukooba et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are reports that HIV and malaria co-infection may occur in any area that has high prevalence of the two infections (14,15) and that much possibilities of deleterious interaction between the two diseases exist in the co-infected patients (5,6,14). Some complications, such as anaemia, which are common to both HIV and malaria are also likely to be worse with the co-infection (16).…”
Section: Introductionmentioning
confidence: 99%